The Effect of Motivation and Work Environment on Employee Performance at PT. Pratomo Putra Teknik, City of Palopo - Meta Meta; Saharuddin; Muammar Khadapi (Jurnal Economic Resource, 2023)
This research was conducted to determine the effect of work motivation and work environment on employee performance at PT. Pratomo Putra Teknik. The population and samples were taken using the Slovin formula, with a total of 40 respondents. The research was conducted by distributing questionnaires to employees of PT. Pratomo Putra Teknik, who studied as many as 40 respondents. The analysis technique used is multiple regression with hypothesis testing, namely the F test and t test. The results of the R square data (R2) are 0.874. The results showed that work motivation and work environment simultaneously affect performance, while the remaining 12.6% are influenced by other factors not examined in this study. Work motivation and work environment together have a positive effect on performance at PT. Praatomo Putra Teknik. The test results show that, partially, there is a significant influence of work motivation on performance at PT. Pratomo Putra Teknik.